Evaluation of disability glare caused by headlights of most common vehicles in Iran - Ahmad Mehri; Milad Abbasi; Seyed Abolfazl Zakerian; Reza Yeganeh; Seyed Hojat Mousavi Kordmiri; Farough Mohammadian; Javad Sajedifar (Archives of Trauma Research, 2021)
Background and Objectives: Road traffic accident is one of the leading causes of death in some countries such as Iran. Disability glare due to headlights of vehicles can increase the risk of crashes and make dangerous conditions. This study aimed to investigate the level of glare induced by the headlights of most common vehicles in Iran. Materials and Methods: This cross-sectional study was conducted in a suburban road of Ilam province in 2019. The disability glare resulted from the headlights of Pride Saba GTX, Pride 131SL, Samand Soren, Peugeot 405, Megan, and Peugeot Pars was measured at the distances of 10–100 m away from the headlights. The Threshold Elevation index under the high-beam and low-beam conditions (headlight's operation modes) was obtained for the background luminance condition including 1 and 50 cd/m2 for the age groups of 20, 35, 70, and 83 years old. Results: When the background luminance was 1 cd/m2, the mean glare level caused by the high-beam mode of illumination exceeded the recommended disability glare thresholds of all age groups. When the background luminance was 50 cd/m2, at certain longitudinal distances, glare level exceeded the disability glare thresholds of the elderly drivers (aged 70 and 83 years). At the background luminance of 1 cd/m2, low-beam mode of illumination caused disability glare at certain distances but not in general. At the background luminance of 50 cd/m2, low-beam mode of illumination did not cause disability glare at any distance. Conclusion: The results showed the mutual effect of luminance and the angle of line of sight with respect to glare source on the emergence of disability glare. The age also exhibited a significant association with the disability glare, as the highest glare levels were obtained for older drivers.